WATERFALL METHOD OF MEDICAL RECORD APPLICATION DEVELOPMENT USING PHP AND MYSQL PROGRAMMING LANGUAGE - Sari Noorlima Yanti; Meti Nurhayati (Journal of Information System, Informatics and Computing, 2023)
The use of computer technology and involvement in people's lives are involved in many aspects of life. One of the applications of computer technology in the health sector is to assist in detecting health problems suffered by the community. Modern society whose daily activities move dynamically certainly needs devices that help in reminding health conditions. One solution to this problem is the use of mobile health applications or M-Health, which tends to increase every year. Based on estimates in the United States, the number of users using these devices is 4500 in 2018 and an estimated increase is at 50,000 users in 2025. Another problem is that most of the current public health history is still recorded manually or not at all. Recording of public health data still uses books and for a long time, of course, these archives can be lost or damaged. One of the uses of this mobile medical history recording application is that the data will always be there. If at any time the user wants to look back at his history, he can just search in this system without having to look in the book and can save time. Current health history as one of the most important conditions in people's lives will provide services. Designing an application is carried out in research based on this problem which can make it easier for users to get their own health information quickly and flexibly using a browser that can be accessed via mobile phones or PCs. As a result of this research, this application will be developed using the waterfall process model and the SDLC (System Development Life Cycle) methodology.